LOOKS: THE DUCHAMP FOREFRONT AS BODY TRANSLATION - Assis, Adriana Carolina Hipólito de (2015)
The look announces beyond the phenomenological field criticism as translation. The avant-garde aesthetic body of Marcel Duchamp world gained strength to revitalized the poetic tradition with irony, with parodic, with pastiches taken from their usual spaces. The museum loses its aura and art reconstructed as great comedy replica of privacy. Virtualizes gaze on the window, the collages of Carrefour, all (classical and popular) lined up on the same shelf : Bombril sold for Monalisa . The look of the Mexican essayist Octavio Paz, as well as concrete poetry, on this context is a look that looked like traits with Duchamp forefront aiming to make a critical and Latin poetry in the breakdown of readymade as a proposal of freedom of aesthetic transgression.